Relationship and effect of duration of first stage of labor on second stage - MN, Leena; Pai, Muralidhar V.; Poojari, Vidyashree G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective: To evaluate the relationship and effect of first stage of labor on second stage. Methods: It was a prospective, observational study. A total of 132 subjects with cephalic presentation at or from 4 cm dilatation with or without intact membrane were included in the study. Women with more than 4 cm dilation were excluded from the study. The duration and complications of second stage were correlated with the duration of first stage. Results: Out of 132 subjects, duration of labor was less than 3 hours in 79 subjects of which 52 (65.8%) had shorter (less than 30 minutes) second stage. The duration of first stage was between 6 and 9 hours in 10 subjects of which 9 (90% had longer (more than 30 minutes) second stage and 4 subjects had first stage lasting more than 9 hours of which 3 (75%) had second stage lasting more than 1 hour. These findings were statistically significant (P = 0.001). As the duration of first stage increased the incidence of instrumental delivery was also increased however this was statistically not significant. Conclusions: As the duration of first stage increases the duration of second stage and the incidence of instrumental/caesarean delivery increases.